Moving From MVP Towards a Product for Environmental Management System: An Action Research - Ribeiro, Rafael C.; Clemente, Willian Giovanni Pires; Bernardino, Maicon (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2026: Anais do XXII Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2026.248699, 2026)
Research Context: Environmental management systems increasingly demand not only regulatory compliance but also technical robustness and scalability to support the daily operations of organizations. Moving beyond a Minimum Viable Product (MVP) towards a consolidated product requires both architectural evolution and systematic validation of new functionalities. Practical Problem: While MVPs provide early validation of market needs, they often lack essential modules and technical maturity. In the environmental domain, this limitation can compromise usability, reliability, and the integration of critical processes such as financial control, commercial proposals, and data management. Proposed Solution: This study reports the technical evolution and structured validation of Suassu, an environmental management platform. Improvements included refactoring the system’s architecture, enhancing scalability, and implementing three new modules: Commercial Management, Financial Management, and Document Management. Related IS Theory: Grounded in Design Science and Technical Action Research under a sociotechnical (People–Process–Technology) lens, which informs iterative artifact evolution and evaluation through established quality and usability constructs. Research Method: Following Action Research methodology, the project was conducted in iterative cycles of diagnosis, planning, action, and evaluation. Validation combined qualitative and quantitative approaches, including functional testing, usability assessment (SUS), Thinking Aloud sessions, and semi-structured interviews. Summary of Results: Results demonstrate improvements in usability, operational efficiency, and user confidence, while also identifying areas for refinement in system integration and consistency. The introduction of dashboards provided strategic value by enabling data-driven decision-making. Contributions and Impact to IS Area: The study contributes by illustrating how MVPs can be systematically evolved into mature, integrated products in regulated domains. It advances Information Systems research by combining technical refactoring, module expansion, and structured validation methodologies within an Action Research framework.